Проектная технология как средство организации самостоятельной работы студентов специальностей естественного направления - Конысбаева, Д.Т.; Омарова, К.И.; Баубекова, Г.К. (My University, 2016)
With the goal of modern education, which consists in the formation of multiple personality, the use of design technology in the educational process is overdue, as it encourages students to self-education and self- organization and the development of research knowledge to solve practical problems. Purpose of the article - to show basic forms of independent work of students of specialties "Biology" and "Geography" technology with project-based learning. In this article, we share experience in this area and provide examples of projects already carried out by students; We emphasize the role of technology in shaping the design of professional and subject specific competences of students.
Keywords: design technology; lifelong learning; classification; self-realized person; the result; group work